Cerebral small-vessel disease at high altitude: A comparison of patients from plateau and plain - Shu, Junlong; Fei, Wen; Zhang, Jing; Li, Fan; Hao, Yu; Ding, Zhijie; Tseyang,; Drolma,; Ji, Shiyong; Zhao, Weiwei; Hu, Yaxiong; Sun, Wei; et al. (Frontiers in Neurology, 2023)
Cerebral small-vessel disease (CSVD) is a worldwide syndrome that has multiple neuroimaging markers such as white matter hyperintensity (WMH) and lacune. The environment of high altitude may have an impact on the pathogenesis and phenotype of CSVD, but the report is scarce. We conducted research to explore the clinical and neuroimaging characteristics of CSVD patients at high altitude. Patients of CSVD residing at high altitude showed more severe WMH but less acute cerebrovascular events and lacunes in neuroimaging, comparing to patients residing at low altitude. Our findings suggest potential biphasic effect of high altitude on the occurrence and progression of CSVD.